Brand turnaround how brands gone bad returned to glory and the seven game changers that made the difference - Post, Karen (McGraw-Hill, 2012)
How did Toyota, Tylenol, and Goldman Sachs bounce back from the brink of destruction? This book reveals the answers and provides valuable lessons for anyone tasked with reviving a brand.